A Lab-Scale Experiment Approach to the Measurement of Wall Pressure from Near-Field under Water Explosions by a Hopkinson Bar - Xiongwei Cui; Xiongliang Yao; Yingyu Chen (Shock and Vibration)
Direct measurement of the wall pressure loading subjected to the near-field underwater explosion is of great difficulty. In this article, an improved methodology and a lab-scale experimental system are proposed and manufactured to assess the wall pressure loading. In the methodology, a Hopkinson bar (HPB), used as the sensing element, is inserted through the hole drilled on the target plate and the bar’s end face lies flush with the loaded face of the target plate to detect and record the pressure loading. Furthermore, two improvements have been made on this methodology to measure the wall pressure loading from a near-field underwater explosion. The first one is some waterproof units added to make it suitable for the underwater environment. The second one is a hard rubber cylinder placed at the distal end, and a pair of ropes taped on the HPB is used to pull the HPB against the cylinder hard to ensure the HPB’s end face flushes with loaded face of the target plate during the bubble collapse. To validate the pressure measurement technique based on the HPB, an underwater explosion between two parallelly mounted circular target plates is used as the validating system. Based on the assumption that the shock wave pressure profiles at the two points on the two plates which are symmetrical to each other about the middle plane of symmetry are the same, it was found that the pressure obtained by the HPB was in excellent agreement with pressure transducer measurements, thus validating the proposed technique. To verify the capability of this improved methodology and experimental system, a series of minicharge underwater explosion experiments are conducted. From the recorded pressure-time profiles coupled with the underwater explosion evolution images captured by the HSV camera, the shock wave pressure loading and bubble-jet pressure loadings are captured in detail at 5  mm, 10  mm, …, 30  mm stand-off distances. Part of the pressure loading of the experiment at 35  mm stand-off distance is recorded, which is still of great help and significance for engineers. Especially, the peak pressure of the shock wave is captured.